Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.35759/janmplsci.v42-1.5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamique des peuplements ligneux dans le Parc National de Manda, au sud du Tchad

Abstract: 1 RÉSUMÉ La présente étude a pour but d’étude la dynamique des peuplements ligneux dans le Parc National de Manda. Elle vise à déterminer les caractéristiques structurales, la composition spécifique et la régénération des peuplements ligneux. Quatre sites ont été implantés depuis 2012. Nous avons procédé à la caractérisation des peuplements ligneux par des relevés dendrométriques. La flore ligneuse dans l’ensemble des sites est riche de 87 espèces reparties en 56 genres et 22 familles. Les sites 1 et 2 ont des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The low richness of species, genera and families in the savannahs (shrub and grassy) would be linked to the strong pressure exerted by the local residents and livestock on the vegetation of these savannahs. Madjimbé et al (2019) revealed in their research in the same area that the most important families are Fabaceae and Combretaceae. Regarding the highest number of genera per family and the most abundant species, these results corroborate the results of Saradoum (2012), Ndotam et al (2017) and Kouyate et al (2020).…”
Section: -Discussion 4-1 Specific Composition Of the Pnmmentioning
confidence: 99%
“…The low richness of species, genera and families in the savannahs (shrub and grassy) would be linked to the strong pressure exerted by the local residents and livestock on the vegetation of these savannahs. Madjimbé et al (2019) revealed in their research in the same area that the most important families are Fabaceae and Combretaceae. Regarding the highest number of genera per family and the most abundant species, these results corroborate the results of Saradoum (2012), Ndotam et al (2017) and Kouyate et al (2020).…”
Section: -Discussion 4-1 Specific Composition Of the Pnmmentioning
confidence: 99%